Effect of Political Stability, Geopolitical Risk and R&D Investments on Environmental Sustainability: Evidence from European Countries by Novel Quantile Models - Depren, Serpil Kilic; Erdogan, Sinan; Kartal, Mustafa Tevfik; Pata, Ugur Korkut (Prague Univ Economics and Business, 2024)
This research investigates the effect of political stability and geopolitical risk on environmental sustainability (ES) by considering R&D investments in nuclear and renewable energy. Considering the high political stability and recent energy crisis and increasing geopolitical risk, the study focuses on three leading European countries. We use the load capacity factor, include data between 1985/1 and 2020/12, and apply quantile on quantile regression (QQ), Granger causality in quantiles (GQ), and quantile regression (QR) models. The study finds that in higher quantiles (i) increasing political stability stimulates the ES in Sweden and the United Kingdom; (ii) increasing geopolitical risk supports the ES in France; (iii) R&D investments increase the ES in all the countries; (iv) there are generally causal effects from the explanatory variables to the ES except some quantiles (0.45-0.50) in all the countries; (v) the power effects of the variables differ according to countries, quantiles and variables.
Keywords: Load capacity factor; political stability; geopolitical risk; European countries; environmental sustainability; ENERGY-CONSUMPTION; CO2 EMISSIONS; HYPOTHESIS; POLLUTION; IMPACT; GREEN; Business & Economics; Government & Law